Headmaster students (PKPGB) of UiTM Sarawak visiting MAMPU - Kipli, Nur Aida; Ramakrishnan, Prabha; Maniam, Yuthandy; Abdullah, Norazlin; Jack, Suriani; Abg Samah, Aizimah; Chiew, Fei Ha (Universiti Teknologi MARA, Sarawak, 2009)
Kuching: A group of 34 headmaster students Program Khas Pensiswazahan Guru Besar (PKPGB) today visited MAMPU Sarawak office at Bangunan Sultan Iskandar. The students are actually half of the third intake group (total 69 admitted in November 2007) of headmasters from several primary schools in Sarawak, and currently studying a course called Quality Management as part of the requirement of the program for the degree of Bachelor of Education (Hons.) in Educational Management at University Teknologi MARA (UiTM) Sarawak.